Arthropoda Community Structure in Conservation Forest and Oil Palm Plantation in Java Tongah Village Area, Hatonduhan District, Simalungun Regency - Silaen, Srinatalia; Barat, Welmar Olfan Basten (Journal of Applied Geospatial Information, 2023)
The research about composition and structure of Arthropoda community was conducted at oil palm plantations Arthropoda were collected at oil palm plantation, conservasion forest and forest edge sites (between conservation forest and plantation area) by survey method with systematic random sampling for arthropoda in litter and soil. A total of four Arthropoda species that belonging to 2 orders, 3 families, 4 general and 57 individuals was collected. The highest number of individuals Isotomiella sp. (14 ind) family Isotomidae. Arthropoda community composition consists of 3 families & 4 species: Neanuridae (Lobella sp.), Brachystomellidae (Brachystomella sp.) & Isotomidae (Isotomiella sp. & Folsomides sp.), Arthropoda community structure The highest density is in the litter location I (16 ind / m2) while the lowest density is in location III (3.56 ind / m2). The highest soil density is in location I (4,538.56 ind / m3) & the lowest density is in location III (789,761 ind / m3). The highest relative density is location III (100%) & the lowest relative density is found in location I (litter, 5.8%) & (soil, 8.9%). The highest Shannon-Wiener diversity index, both litter and soil, were found in location I (litter 1.28) & (soil, 1.38) and the lowest diversity index was found in location III (0). The highest similarity index for Sorensen was location III (75.71%) and the lowest was the comparison between locations II & I (20%).